Improved cancer detection in Waldeyer’s tonsillar ring by 68Ga-FAPI PET/CT imaging - Serfling, Sebastian; Zhi, Y.; Schirbel, A.; Lindner, Thomas; Meyer, T.; Gerhard-Hartmann, E.; Lapa, C.; Hagen, R.; Hackenberg, S.; Buck, A. K.; Scherzad, A. (European journal of nuclear medicine and molecular imaging, 2021)
In cancer of unknown primary (CUP), positron emission tomography/computed tomography (PET/CT) with the glucose analog [18F]FDG represents the standard imaging approach for localization of the malignant primary. Frequently, however, [18F]FDG PET/CT cannot precisely distinguish between small occult tumors and chronic inflammation, especially in Waldeyer’s tonsillar ring. To improve the accuracy for detecting primary tumors in the Waldeyer’s tonsillar ring, the novel PET tracer [68Ga]Ga-FAPI-4 for specific imaging of fibroblast activation protein (FAP) expression was used as a more specific target for cancer imaging.
"Published online: 15 October 2020".- S. 1178
Im Titel ist "68" bei "Ga-FAPI" hochgestellt
Gesehen am 09.09.2024